Heuristic evaluation of the smartphone applications in supporting elderly - Salman, H.M. (2019)
Elderly people often experience deterioration in cognitive and physical traits, which impacts their ability to use smartphone applications. Because of this age-related deterioration, designers should pay special attention when it comes to designing user interfaces (UIs) for elderly users. Nevertheless, the typical modern UI apparently is not optimised for this group of users. Our primary objective is to answer the research question: what are the usability problems that could be potentially experienced by elderly as they interact with the user interfaces of smartphones? A further objective is to recommend improvements in the design of UIs that can particularly benefit elderly users. Five individual experts applied a heuristic evaluation method within a controlled environment to determine the anticipated usability problems in the two case study applications i.e., alarm and camera. Analysing the identified usability problems revealed that they were attributed to three issues that the UI failed to adhere to; promote recognition over recall, improve userâs efficiency of use, and achieve an intuitive and consistent interface. Experts have suggested solutions that would help tackle these issues and provide insights regarding potential improvements for designing elder-friendly UIs. Â© Springer Nature Switzerland AG 2019.